Intelligent Shoes - RS Sdn. Bhd. / Siti Ruziyana Yatim - Yatim, Siti Ruziyana (2020)
The concept of an Intelligent Shoes is about a shoes that has a function of massaging that easy to use and carry anywhere. The vibrating technology is used to massage the foot. Other that that, an application is used to control the motion of massaging where an application can be downloaded at Play Store for free. To activate the shoes and connect to the apps, user id for the shoes is use button on/off use for customer to on or off the shoes. Furthermore, an Intelligent Shoes also us e a material that water resistances to make sure that the product could be long lasting and protect from water. Our target market form any level of age started from 13 years old who has a foot problem and people who always care about their health. Other than that our target customer are from medium to high level income because we selling the product from medium range that affordable for people to buy the product.